2016
DOI: 10.1093/ckj/sfw007
|View full text |Cite
|
Sign up to set email alerts
|

Fat tissue and inflammation in patients undergoing peritoneal dialysis

Abstract: BackgroundBody weight has been increasing in the general population and is an established risk factor for hypertension, diabetes, and all-cause and cardiovascular mortality. Patients undergoing peritoneal dialysis (PD) gain weight, mainly during the first months of treatment. The aim of this study was to assess the relationship between body composition and metabolic and inflammatory status in patients undergoing PD.MethodsThis was a prospective, non-interventional study of prevalent patients receiving PD. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Also, the exact mechanism by which dyslipidemia affects a higher risk of all-cause technique failure remains unclear. On the other hand, the association between pro-atherogenic lipid profile and longer PD duration [26], a decrease in RRF [20], [27] and glucose absorption from the dialysis fluid [28], [29] can be a possible explanation of a higher risk of all-cause technique failure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the exact mechanism by which dyslipidemia affects a higher risk of all-cause technique failure remains unclear. On the other hand, the association between pro-atherogenic lipid profile and longer PD duration [26], a decrease in RRF [20], [27] and glucose absorption from the dialysis fluid [28], [29] can be a possible explanation of a higher risk of all-cause technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed a significant decrease in residual diuresis in dyslipidemia conditions. Additionally, fluid and weight control problems are common amongst PD patients and may be accompanied by dyslipidemia [16], [20], [25], [29], [31]. Rincón et al found the mean increase in fat mass of 3.0 ± 3.2 kg/year during the 26-month-follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas a low LTI was related to FO and inflammation, the study of Lee et al showed that in male subjects, the FM/LTM ratio was also positively related to hsCRP and interleukin‐6 . In PD patients, changes in FTI were also positively related to changes in inflammatory status . This has mainly been attributed to the relation between visceral adiposity and systemic inflammation .…”
Section: Association Of Abnormalities In Body Composition With Other mentioning
confidence: 99%